Consumer Spending and the Rate of Inflation - Springer, William L. (The Review of Economics and Statistics, 1977)
IN a recent article, Thomas Juster and Paul Wachtel (1972b) have examined the impact of the rate of inflation on consumer expenditures. Using survey data on individuals' expectations regarding the future rate of inflation, they concluded that inflationary expectations cause a reallocation of consumer expenditures. In particular, their analysis showed that a higher expected rate of inflation results in increased expenditures on nondurables and services and a decline in spending on durables. This article examines their findings and presents a different set of conclusions using objective measures of inflationary expectations based on past actual rates of inflation.